Integration of Public Transportation in Smart Transportation System (Smart Transportation System) in Jakarta - Rizqita Oktorini; Lita Sari Barus (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2022)
Congestion is not a new problem for Jakarta, as the center of government and a metropolitan city in Indonesia. Handling the congestion problem in Jakarta then requires a comprehensive and comprehensive solution. Smart cities and smart transportation systems are thought to be able to do just that. This paper aims to review the existing smart transportation system in Jakarta and attempt to integrate public transportation into this system as an effort to overcome congestion in Jakarta. The review in this paper is carried out qualitatively by reviewing various literatures that have been published previously. The results show that the government has started trying to develop a smart city through the Jakarta Smart City (JSC) so that the development of a smart transportation system as part of a smart city is needed. In this case, this paper has developed a framework for a smart transportation system that integrates the public transportation system into it so that a more integrated smart transportation system is created for Jakarta.